Effects of Local Gravity Compensation on Motor Control During Altered Environmental Gravity - Kunavar, Tjasa; Jamšek, Marko; Barbiero, Marie; Blohm, Gunnar; Nozaki, Daichi; Papaxanthis, Charalambos; White, Olivier; Babič, Jan (Frontiers in Neural Circuits, 2021)
Our sensorimotor control is well adapted to normogravity environment encountered on Earth and any change in gravity significantly disturbs our movement. In order to produce appropriate motor commands for aimed arm movements such as pointing or reaching, environmental changes have to be taken into account. This adaptation is crucial when performing successful movements during microgravity and hypergravity conditions. To mitigate the effects of changing gravitational levels, such as the changed movement duration and decreased accuracy, we explored the possible beneficial effects of gravity compensation on movement. Local gravity compensation was achieved using a motorized robotic device capable of applying precise forces to the subject’s wrist that generated a normogravity equivalent torque at the shoulder joint during periods of microgravity and hypergravity. The efficiency of the local gravity compensation was assessed with an experiment in which participants performed a series of pointing movements toward the target on a screen during a parabolic flight. We compared movement duration, accuracy, movement trajectory, and muscle activations of movements during periods of microgravity and hypergravity with conditions when local gravity compensation was provided. By using local gravity compensation at the arm, we were able to mitigate the changes in movement duration, accuracy, and muscle activity. Our results suggest that the use of such an assistive device would help with movements during unfamiliar environmental gravity.